REFLEKSI KONSEPSI HADRATUS SYECH KH. HASYIM ASY-‘ARI TENTANG KOMPETENSI KEPRIBADIAN GURU DALAM KITAB ADABUL ‘ALIM WAL MUTA’ALLIM DI MTsN 14 JOMBANG - Nita Ayu Rahmawati; Hidayatur Rohmah (Universitas KH. A. Wahab Hasbullah, 2019)
This study aims to determine the personal competence of MTsN 14 Jombang teacher reflected in the book Adabul abul Alim Wal Muta’allim by Hadratus Syech KH Hasyim Asy’ar about Teacher Ethics. Where the teacher's personal competence can shape the learner's personality as assessed from his spiritual and social attitudes. This research is a descriptive research with a qualitative approach. The data generated from this research are in the form of descriptive data obtained from data in the form of writing, words, and documents originating from respondents or sources studied. Researchers used purposive sampling techniques in the stage of field work, purposive sampling is a sampling technique for data sources with certain considerations. Therefore, the respondents in this study were all teachers who taught in class IX MTsN 14 Jombang and students determined using radom. The results showed that, the competence of MTsN 14 Jombang teachers in accordance with the Teacher Performance Assessment was included in both categories. Also from observations that show that the competencies of teachers who teach MTsN 14 Jombang meet the personal competency standards of teachers in accordance with the Minister of National Education Regulation No. 16 of 2007. Then for students of class IX MTsN 14 Jombang they already have a good personality, things this is shown from the practice of spiritual attitudes and social attitudes that show that of thirty attitude indicators there are only seven indicators that are less mastered by some students. Thus, the personality possessed by educators will have an impact on the development of the learner's personality